2012
DOI: 10.5505/tjb.2012.30602
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D correlation between mother and baby during pregnancy in the winter

Abstract: ÖZETAmaç: Çalışmamızda kış aylarında gebelerdeki D vitamini düzeylerinin bebeklere nasıl yansıdığını araştırmayı amaçladık. Gereç ve Yöntemler:Çalışmaya 37 haftayı doldurmuş 250 sağlıklı gebe dahil edildi. Gebelerden doğum öncesi travay odasında, bebeklerinden ise doğum sırasında göbek kordonundan venöz kan alındı. Örneklerin 25(OH)D düzeyleri kemilüminesan immun ölçüm yöntemi ile Diasorin Liaison cihazında çalışıldı. Bulgular: Annelerin D vitamini ortalaması 11,5 ± 5,9 ng/mL iken kordon kanında bu değer 10,9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Nonetheless, all of these data confirm that vitamin D deficiency continues to be a problem in pregnant women in Turkey and their infants. It has been reported that the level of vitamin D in pregnant women can be affected by factors such as geographical region, sunbathing habits, style of dress, body mass index, the educational level of the mother, socioeconomic status, dairy product consumption, and external vitamin D supplementation [6][7][8][9][10][11][12]. It was observed in this meta-analyses study that rate of vitamin D deficiency varied from 57% to 93% for infants and from 62% to 95% for pregnant women.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Nonetheless, all of these data confirm that vitamin D deficiency continues to be a problem in pregnant women in Turkey and their infants. It has been reported that the level of vitamin D in pregnant women can be affected by factors such as geographical region, sunbathing habits, style of dress, body mass index, the educational level of the mother, socioeconomic status, dairy product consumption, and external vitamin D supplementation [6][7][8][9][10][11][12]. It was observed in this meta-analyses study that rate of vitamin D deficiency varied from 57% to 93% for infants and from 62% to 95% for pregnant women.…”
Section: Discussionmentioning
confidence: 74%
“…In another study performed by Ergur et al [10], 18.6% of the mothers and 2.9% of the neonates had normal vitamin D levels. Yildiz et al [11] found a mean 25(OH) D3 level of 11.5±5.9 ng/mL and 10.9±5.9 ng/mL for mothers and infants, respectively, during winter months. Gülez et al [12] found a prevalence of vitamin D deficiency of 31% in a study of 100 infants in Izmir aged 0-24 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortified food with vitamin D is negligible in Turkey. The prevalence of vitamin D deficiency is considerable size is seen in our country 7 as overall the world. The objective of the present study was to determine prevalence of vitamin D deficiency in children whose serum vitamin D levels measured in our laboratory and to show effect of age, gender and seasons on vitamin D levels.…”
Section: Introductionmentioning
confidence: 99%
“…While fetal calcium levels are higher than maternal calcium levels during pregnancy, the concentration of vitamin D in umbilical cord blood and maternal vitamin D levels are similar. [16][17][18][19][20] Although many studies have been conducted examining the relationship between maternal preeclampsia and vitamin D level, a limited number of studies have evaluated the vitamin D level in the cord blood of preeclamptic mothers.…”
Section: Introductionmentioning
confidence: 99%